1999
DOI: 10.1590/s0103-84781999000100011
|View full text |Cite
|
Sign up to set email alerts
|

The tof-guard neuromuscular transmission monitor and its use in horses

Abstract: It has been emphasized in the human medical literature, that when using a neuromuscular blocking agent, it is of vital importance the monitoring of the neuromuscular block and that these agents should never be used without it. The purpose of this study was to evaluate the use of the neuromuscular transmission monitor TOF-Guard in horses. Twelve horses were randomly assigned whether to receive pancuronium or atracurium as the neuromuscular blocking agent. All horses were pre-medicated with romifidine, anaesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…1983) with mechanomyography has been reported. Acceleromyography is a relatively new technique for monitoring neuromuscular blockade and Bechara et al. (1999) used different nerve‐muscle units to demonstrate that the acceleromyography was a reliable technique in horses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1983) with mechanomyography has been reported. Acceleromyography is a relatively new technique for monitoring neuromuscular blockade and Bechara et al. (1999) used different nerve‐muscle units to demonstrate that the acceleromyography was a reliable technique in horses.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the peroneal nerve (Klein et al 1983) with mechanomyography has been reported. Acceleromyography is a relatively new technique for monitoring neuromuscular blockade and Bechara et al (1999) used different nerve-muscle units to demonstrate that the acceleromyography was a reliable technique in horses. Stimulation of the peroneal nerve with an acceleromyograph, in the manner described, was feasible in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations